Policy prioritization for sustainable village fund management using AHP and a Modified Delphi approach in Padangsidimpuan City, Indonesia - Batubara, Silviana; Purnama, Nadia Ika; Syafii, Ahmad (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2026)
Rural development has become a central component of Indonesia's sustainable development agenda, particularly through the implementation of the Village Fund program, which aims to improve community welfare and reduce regional disparities. This study examines the current state of Village Fund management in Padangsidimpuan City and identifies strategic policy priorities to promote sustainable village development. An explanatory sequential mixed-methods design was employed, integrating a structured expert consensus approach based on selected principles of the Modified Delphi technique with the Analytic Hierarchy Process (AHP). The expert consensus process was used to identify and validate the key criteria, sub-criteria, and policy alternatives, while AHP was applied to determine their relative priority weights. The results indicate that Village Governance is the most important criterion (0.332), followed by Community Social and Human Resources (0.256) and Village Economy (0.220). At the policy level, Strengthening Village Governance and Accountability emerged as the highest-priority alternative (0.239), followed by Community Economic Empowerment (0.206) and Human Resource Development and Social Services (0.202). Sensitivity analysis confirmed that the priority rankings remained stable across multiple weighting scenarios, demonstrating the robustness of the proposed decision-making model. Methodologically, this study contributes an integrated policy prioritization framework that combines a structured expert consensus approach with multicriteria decision analysis to support evidence-based and context-sensitive Village Fund governance. In practice, the findings guide village and regional governments in formulating more transparent, participatory, and sustainable Village Fund policies.